A STUDY ON MALAYSIAN ENGLISH LANGUAGE TEACHERS’ READING HABITS: TYPES OF MATERIALS READ AND RATE OF EXTENSIVE READING - Sharmila a/p Appa Rwoo; Chew Fong Peng; Huzaina Abdul Halim, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This study is carried out with the purpose of gaining more in-depth information in regard to the reading habits of 210 English Language (EL) teachers in the district of Klang, Selangor. A convenient sampling method is used to choose the respondents while data are gathered with a survey questionnaire. The first aim of this study is to study the types of materials read by ESL teachers. Secondly, it aims to identify the rate of extensive reading among these teachers. The results show that ESL teachers read mostly light reading materials online and shun heavy materials. The researcher also discovered that the rates of extensive reading among ESL teachers are average to high. Therefore, the Ministry of Education could implement nationwide reading programmes and teachers should take the initiative to read more.